Electronic Marketing Training For Small Businesses With Disabilities (E-Marketing Training For Diffable Small Business) - Edward Delali Darku (CV. AFDIFAL MAJU BERKAH, 2023)
The business problem experienced by disabled partners Ida Modiste is not knowing how to market services electronic. Starting from this problem and the results of the survey, the partners agreed to market their services electric. The purpose of tranning electronic marketing assistance is a form of PKM activities and partnering with Ida Modiste (disabled). Through partners namely Ida Modiste (disabled) is so that the income of partners increases through marketing services from manual marketing to electronic marketing. The PKM method includes: (1) providing electronic marketing of tranning, (2) electronic marketing assistance. The results of PKM activities are increased understanding and skills of partners in terms of marketing services online, and the publication of mass media, as well as the existence of scientific articles published in PKM journals.